Transformation of Elementary Science Learning with the Project Based Learning Model - Rahma santhika; Rohmani (International Journal of Elementary Education, 2025)
This study focuses on the effectiveness of using Project Based Learning (PJBL) in learning Natural Sciences in elementary schools. PJBL is a project-based learning model that encourages students to actively participate in investigation, exploration, and problem solving through projects that are relevant to the learning material. This model is considered capable of improving conceptual understanding, critical thinking skills, and active involvement of students in science learning. This study uses the Systematic Literature Review approach by analyzing articles from the Google Scholar database published between 2019 and 2024. From a total of 261 initial documents, 8 articles were selected based on eligibility criteria, such as relevance to the topic, accessibility, and publication quality. The results showed that the implementation of PJBL was effective in improving student learning outcomes, problem-solving skills, and learning motivation. In addition, PJBL also encourages students to work collaboratively, think creatively, and be more independent in understanding science concepts. The implication of this study is that PJBL can be an innovative learning model that helps teachers create more interactive and meaningful learning experiences. Therefore, support is needed in the form of teacher training and provision of adequate resources so that PJBL can be implemented optimally in elementary schools.